(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
Writing about the different forms of madness, illness, and the body in the texts of Spanish American writers is not an easy task. The eleven essays gathered here dismantle the most subtle aspects of the fable that has been woven about women over time, and place us before the following questions: What does this obsessive writing about madness, illness, and the body represent? in Latin American literature, and why the need to dive, precisely, into the deepest and most painful areas of feminine discourse? (Review)